Legal Scientific Philosophical Fundamentals Sharia Economics - Muhammad Yunus; Muhamad Maulana Darsono; Hasan Bisri; Ija Suntana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Islamic economics is an economic system based on Islamic teachings and values derived from the Koran and As-Sunnah Ijma and Qiyas or other sources. The goal is to seek the pleasure of Allah and the methods are not contrary to His Sharia. Economic activities, whether production, consumption, exchange, and distribution, are tied to divine principles and divine goals. This research aims, First: To find out the philosophical foundations of Sharia economics, Second: To find out the differences between the Capitalist, Socialist and Islamic economic systems. The approach method used in this research is normative juridical with descriptive analytical research nature. The types of data used in this research are primary and secondary data. This research is classified as a type of qualitative research. The results of this study indicate that: First, the basics of Sharia economics are based on Tawhid, Khilafah and 'Adalah, namely the Establishment of Justice between fellow human beings, the achievement of maslahah. Second: The Islamic Economic System is between the Capitalist and Socialist economic systems, both in terms of paradigms, bases and philosophical foundations.